PERENCANAAN STRUKTUR BAJA PADA PEMBANGUNAN APARTEMEN 7 LANTAI DI JALAN PARIT H HUSIN II: PERENCANAAN STRUKTUR BAJA PADA PEMBANGUNAN APARTEMEN 7 LANTAI DI JALAN PARIT H HUSIN II - rahmadani, rini; Miranda, Mia Amalia; Anggraini, irene (RETENSI, 2021)
Having a place to live like an apartment is an alternative solution for the population that is not comparable to land for building a place to live. Steel has been used for a long time because of its advantages compared to other materials such as concrete. Steel structure planning refers to SNI 1729-2015 (Specifications for structural steel buildings), SNI 1727-2013 (Minimum load for designing buildings and other structures), PPPURG 1987 (Guidelines for loading planning for houses and buildings), SNI 1726-2019 (Earthquake Resistance Planning for Buildings and Non-Buildings) and others. The analysis was carried out with ETABS software, the calculation results obtained that the thickness of the floor plate was 9 cm, beam dimensions used IWF profiles 450.200.9.14, IWF 506.201.11.19, IWF 400.200.8.13, IWF 800.300.14.26, and IWF 700.300.12.24, column dimensions using H profiles 538.477.90.90, and the H profile 418.417.30.30. The structural connection is planned as a connection with high bolt quality, namely A325.